Sulfanilic Acid-catalyzed Synthesis of 4-arylidene-3-substituted isoxazole-5(4H)-ones - Kiyani, Hamzeh; Mosallanezhad, Asiyeh (Current Organic Synthesis, 2018)
Aim and Objective: In recent studies, chemistry of heterocyclic compounds, especially isoxazoles, has been widely considered by organic chemistry researchers because they have been found in many molecules, including naturally occurring bioactive compounds, pharmaceuticals, and agrichemicals. Isoxazol- 5(4H)-ones and their derivatives, on the other hand, have significant biological properties can be mentioned as examples of antibacterial, anti-inflammatory, antifungal, anticancer, analgesic, fungicidal, and insecticidal activities. Therefore, the development of ecofriendly methods, such as three-component processes, for the synthesis of isoxazol-5(4H)-ones is highly desirable. This work focus on the one-pot, three-component reaction (3-CR) of aldehydes, hydroxylamine hydrochloride, and three β-ketoester using catalytic amounts of sulfanilic acid (SA) aimed at the synthesis of isoxazol-5(4H)-ones. Another aim of this study is to use water as a green solvent for the above-mentioned 3-CR. Materials and Methods: Using SA as an efficient organocatalyst, the multicomponent cyclocondensation of aromatic/hetero-aromatic aldehydes, hydroxylamine hydrochloride, and ethyl acetoacetate/ethyl 4- chloroacetoacetate/ethyl benzoylacetate has been implemented. The reactions were carried out in water as a green solvent at room temperature. The corresponding heterocyclic products were separated by simple filtration and washing with water. Also, the solvent was removed from the filtrate by evaporation to recycle the catalyst. Results: It was found that SA act as the catalyst for the synthesis of 4-arylidene-3-substituted isoxazole-5(4H)- ones via three-component reaction of aromatic/hetero-aromatic aldehydes, hydroxylamine hydrochloride, and three β-dicarbonyl compounds (ethyl acetoacetate, ethyl 4-chloroacetoacetate, and ethyl benzoylacetate). Optimization of the catalyst quantity and solvent showed that the highest yield was achieved with 20 mol% of SA in aqueous media. 4-Arylidene-3-substituted isoxazole-5(4H)-ones have been successfully synthesized in the presence of SA catalyst. Conclusion: The SA catalyst could be recovered easily from the filtrate via evaporation of solvent and reused many times. The present synthetic method is a simple, green, clean, and environmentally friendliness alternative for synthesizing 4-arylidene-3-substituted isoxazole-5(4H)-ones. Reactions were performed without the use of heating, microwave and ultrasound irradiations.
Keywords: 4-Arylidene-3-substituted isoxazole-5(4H)-ones